New lights on Batu Aceh Muslim gravestones in Pulau Pinang, Malaysia - Muhammad Nabil, Ahmad Nadri; Zakariya, Hafiz (2019)
Batu Acehs, literally denotes “Aceh stones” are among the most intriguing artefacts in the study of history and civilisation of Islam in the Malay world. Among the old Muslim gravestones, the style known as Batu Aceh, originated from the Aceh region in northern Sumatera. They serve as the premiere primary sources for the study of the classical Malay-Islamic polities which dominated the region from 13th to 19th century CE. It is estimated that there are over 500 Batu Aceh across the Malay Peninsula. Furthermore, around 5000 Aceh gravestones have been identified in various parts of the Malay Archipelago. They were mostly erected by local community to mark the demise of persons of high status from among royalties and nobilities. This study focuses on Batu Aceh in Pulau Pinang because the Aceh stones in this state of has been forgotten, neglected and understudied. Only two(2) pairs of Batu Aceh at the Masjid Melayu Lebuh Aceh and Tanjong(pre-colonial name for Georgetown) are well-known and significantly covered by modern scholarship. This study is also important because Pulau Pinang was an integral part of the old Kedah sultanate, a renowned entrepot from 18th to the early 20th centuries. This status attracted rulers, traders and scholars from all around the world, especially Aceh to come to Kedah Sultanate before the establishment of British colony there in 1786 CE. There are numerous quantity of Batu Aceh in the Kedah Sultanate; however only small number of Batu Aceh in Pulau Pinang is recorded. Therefore, this study intends to present the preliminary results of the archaeological and historical analyses of Batu Aceh discovered at eight new sites throughout Pulau Pinang. Moreover, it provides other important information such as an annotation, distribution analysis, typology (forms and features), and historical context.